The image of Native Americans in Listy z podróży do Ameryki by Henryk Sienkiewicz in the context of articles from „Wędrowiec”. Part I. Ways of naming representatives of Native American population - Pietrzak, Magdalena (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The aim of the paper is to present a linguistic image of native inhabitants of North America outlined by Henryk Sienkiewicz in Listy z podróży do Ameryki. The author excerpted from the Listy the lexicon used to name representatives of Native American population and compared it with the lexicon coming from articles published in the journal „Wędrowiec”. She analyzed names of Native Americans and their tribes, paying attention to variation of names, synonyms, derivatives, appellative forms, multiword expressions (neutral and marked), metaphorical expressions, scopes of names and textual context in which they had appeared.